Guideline‐Directed Medication Use in Patients With Heart Failure With Reduced Ejection Fraction in India: American College of Cardiology's PINNACLE India Quality Improvement Program. Issue 3 (16th February 2016) - Pokharel, Yashashwi; Wei, Jessica; Hira, Ravi S.; Kalra, Ankur; Shore, Supriya; Kerkar, Prafulla G.; Kumar, Ganesh; Risch, Samantha; Vicera, Veronique; Oetgen, William J.; Deswal, Anita; Turakhia, Mintu P.; et al.
Abstract: Little is known about the use of guideline‐directed medical therapy (GDMT) in outpatients with heart failure with reduced left ventricular ejection fraction (HFrEF; ≤40%) in India. Our objective was to understand the use of GDMT in outpatients with HFrEF in India. The Practice Innovation And Clinical Excellence (PINNACLE) India Quality Improvement Program (PIQIP) is a registry for cardiovascular quality improvement in India supported by the American College of Cardiology Foundation. Between January 2008 and September 2014, we evaluated documentation of use of angiotensin‐converting enzyme inhibitors (ACEIs)/angiotensin receptor blockers (ARBs) and β‐blockers, or both, among outpatients with HFrEF seeking care in 10 centers enrolled in the PIQIP registry. Among 75 639 patients in the PIQIP registry, 34 995 had EF reported, and 15 870 had an EF ≤40%. The mean age was 56 years; 23% were female. Hypertension, diabetes, coronary artery disease, and myocardial infarction were present in 37%, 23%, 27%, and 17%, respectively. Use of ACEIs/ARBs, β‐blockers, and both were documented in 33.5%, 34.9%, and 29.6% of patients, respectively. The documentation of GDMT was higher in men, in patients age ≥65 years, and in those with presence of hypertension, diabetes, or coronary artery disease. Documentation of GDMT gradually increased over the study period. Among patients enrolled in the PIQIP registry, about two‐thirds of patients with EF ≤40% did not have documented receipt of GDMT. This study is an initial step toward improving adherence to GDMT in India and highlights the feasibility of examining quality of care in HFrEF in a resource‐limited setting.